Curtir e compartilhar: periódicos científicos da educação na web social - Amanda Tolomelli Brescia (2017)
In this investigation, we analyzed the presence and online attention of the journals indexed to the SciELO Brazil collection. In order to do so, we reflect on basic concepts of scientific journals, social webs and the traditional metrics and alternatives for measuring scientific impact. The empirical research aimed at mapping and characterizing the journals clipping consisting of 19 journals stratified in Education by Qualis Periodicals and identifying their presence and performance in the social web tools. Alternative metrics were also considered to measure the scientific and social impact so as to evaluate the attention driven towards the articles in the periodicals. The performance was analyzed according to the types of behaviors, when adhering to social web tools such as social webs, blogs, websites and the possible metrics to be used by such journals - and the alternative metrics, in turn, through comparative analysis between altmetric.com services and the Facebook API. Findability in periodicals was high, but the analysis of the data collected showed that the online presence of these journals is still rather discreet. It is considered that online attention reflects the discrete presence, being scarcely expressive too. The aim was to identify good practices and issues to be considered by periodical editors so that the circulation of published scientific knowledge achieves significant results in the alternative metrics of scientific and social impact. Throughout the development of the research, the following equation was taken into consideration: alternative metrics + traditional bibliometrics = future metrics, an allusion to the non-substitution of metrics, but rather to the need for a shared, complementary action, seeking to reach the metrics of the future and describe a more complete picture of scientific communication.